Pengaruh Electronic Word of Mouth terhadap Minat Beli Reservasi Hotel - Rusyaima Farha Salsabila; Ekayana Sangkasari Paranita (Neolectura, 2020)
This research is motivated by the increasing number of internet users used as promotional media by online travel agents. This study will analyze the effect of electronic word of mouth on the interest in buying hotel reservations via the Traveloka application, both from the perspective of intensity, the valence of opinion, and content. In this study, researchers used quantitative methods. This research collects data by distributing questionnaires via a google form, which are distributed to people who have made hotel reservations through the Traveloka application. The data analysis method used is the Multiple Linear Regression. The results showed that partially the intensity and content variables had a significant positive effect on buying interest in hotel reservations, but simultaneously the three variables had a significant positive effect on buying interest in hotel reservations.